For Intellectual Liberty. Bulletin, No. 1 - Bernal, J. D. (John Desmond), 1901- ; Carter, W. Horsfall (William Horsfall), 1900-1976; Huxley, Aldous, 1894-1963 ([London] : For Intellectual Liberty (London, England))
1936-11 SA15-005-010 32 pages 15X/1/84/1